I Saw a Ant in a Parking Lot - Prince, Joshua; Pamintuan, Macky (USA, 2007)
Dorothy Mott, a parking lot attendant, must think fast to save an ant who is looking for goodies right in the path of a minivan...
Keywords: Animal Story; Ants - Packing Lot; Juvenile Fiction